2014
DOI: 10.1016/j.rmed.2014.07.014
|View full text |Cite
|
Sign up to set email alerts
|

The growing epidemic of water pipe smoking: Health effects and future needs

Abstract: Water pipe smoking (WPS), an old method of tobacco smoking, is re-gaining widespread popularity all over the world and among various populations. Smoking machine studies have shown that the water pipe (WP) mainstream smoke (MSS) contains a wide array of chemical substances, many of which are highly toxic and carcinogenic for humans. The concentrations of some substances exceed those present in MSS of cigarettes. Despite being of low grade, current evidence indicates that WPS is associated with different advers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
74
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(76 citation statements)
references
References 106 publications
0
74
0
1
Order By: Relevance
“…Novel biomedical research has revealed that WTS may result in worse lung functioning as a result from longer sustained volumes of inhaled smoke during a WTS session exposing individuals to similar types of carcinogens and toxic heavy metals found in cigarette smoke (Akl et al, 2010). Along with WTS demonstrating similar health risks as cigarette use, (Bou Fakhreddine, Kanj, & Kanj, 2014) WTS has also been linked to nicotine dependence (Cobb, Ward, Maziak, Shihadeh, & Eissenberg, 2010). Although evidence highlights the negative health effects of WTS, the general perception of WTS is that it is less harmful than cigarettes (Rezk-Hanna, Macabasco-O’Connell, & Woo, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Novel biomedical research has revealed that WTS may result in worse lung functioning as a result from longer sustained volumes of inhaled smoke during a WTS session exposing individuals to similar types of carcinogens and toxic heavy metals found in cigarette smoke (Akl et al, 2010). Along with WTS demonstrating similar health risks as cigarette use, (Bou Fakhreddine, Kanj, & Kanj, 2014) WTS has also been linked to nicotine dependence (Cobb, Ward, Maziak, Shihadeh, & Eissenberg, 2010). Although evidence highlights the negative health effects of WTS, the general perception of WTS is that it is less harmful than cigarettes (Rezk-Hanna, Macabasco-O’Connell, & Woo, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…First, most ANTPs appear to have adverse health effects, including increasing users’ risk of cardiovascular and respiratory disease as well as cancer [1417]. An additional concern is the potential impact of ANTP use on cigarette smoking.…”
Section: Introductionmentioning
confidence: 99%
“…Using the sale of cigarettes as an example, there is abundant evidence that cigarettes sold singly are affordable to children (16) and that proximity of tobacco vendors close to school grounds may influence tobacco use (17). Cultural factors may play a part: in some countries it remains appropriate to give and receive tobacco as part of business transactions (18); other forms of tobacco, such as the water pipe, enjoy social acceptability that is difficult to tackle (19). Adolescents are vulnerable to targeted marketing strategies by the tobacco industry.…”
mentioning
confidence: 99%